Monitoring visit on the governance of postgraduate programme processes and procedures at the faculty of pharmacy - Ahmad Kamal, Syahida Fathiah (Faculty of Pharmacy, 2025)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) recently received a monitoring visit focused on the governance of postgraduate programme processes and procedures by the Institute of Postgraduate Studies (IPSis) on 19 March 2025. This visit formed part of IPSis' strategic initiative to ensure that the management of postgraduate programmes across all faculties is carried out in line with the policies and guidelines set by the university and the Ministry of Higher Education (MOHE).